Effectiveness of the PBL model on mathematics learning to cultivate mathematical literacy of elementary school students - Jannah, Ma`rifatul; Habiby, Wahdan Najib (Universitas Islam Raden Intan Lampung, INDONESIA, 2022)
This study aims to determine the effectiveness of the Problem-Based Learning model on mathematics learning to instill mathematical literacy in elementary school students. Quasi Experiment was chosen as the type of this research. The research population was the 5th-grade students at SD Muhammadiyah 08 Cilacap, with the research sample consisting of two classes, namely 5A and 5B. The instruments used are test and non-test instruments. Hypothesis testing was carried out using the independent sample t-test and paired sample t-test. The average score on the pretest before the treatment was 59.7 in class 5A and 55.95 in class 5B. The average pretest score in class 5A was 66.6, and 62.15 in class 5B. The post-test average score was 77.7 in class 5A and 91.8 in class 5B. The study results show that the PBL model influences the mathematical literacy of elementary school students and increases students’ learning outcomes.